A MODEL FOR INCREASING THE DIGITALIZATION OF ISLAMIC MICROFINANCE INSTITUTIONS (LKMS) AS ECONOMIC DEVELOPMENT OF ISLAMIC BOARDING SCHOOLS - Apriyana, Maya; Purnamasari, Lise; Zahra, Umu Saidah Fatimah; Tsani, Adil Mu’ti (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study aims to determine the model for increasing the digitalization of Islamic microfinance institutions as the economic development of Islamic boarding schools. The model for increasing digitalization as the economic development of Islamic boarding schools is determined in this study using the Analytical Network Process (ANP) method with decision-making by considering and validating empirical experience. Data collection techniques using questionnaire distribution techniques and interviews. The results of this study indicate that the most appropriate model is the development of SMFI. This model focuses on the development of SMFIs by providing financing to the business units of Islamic boarding schools so that they can develop the economy of Islamic boarding schools independently. Alternatives to create financial digitalization and economic development of Islamic boarding schools are carried out by training managers, adding quality human resources, and collaborating with other parties.